2009
DOI: 10.1371/journal.pone.0007514
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Molecular Determinants of Primary HIV-1 Vpr Proteins: Impact of the Q65R and R77Q Substitutions on Vpr Functions

Abstract: Although HIV-1 Vpr displays several functions in vitro, limited information exists concerning their relevance during infection. Here, we characterized Vpr variants isolated from a rapid and a long-term non-progressor (LTNP). Interestingly, vpr alleles isolated from longitudinal samples of the LTNP revealed a dominant sequence that subsequently led to diversity similar to that observed in the progressor patient. Most of primary Vpr proteins accumulated at the nuclear envelope and interacted with host-cell partn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
39
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 47 publications
4
39
1
1
Order By: Relevance
“…This suggests the function of MUS81-EME1 down-regulation by Vpr is independent of its activity in G 2 arrest. An analysis of Vpr Q65R, another mutant defective in G 2 arrest (22,25,28,37), further supports this conclusion (Fig. 5, E and F).…”
Section: Vpr Down-regulates Mus81-eme1 By the Crl4-dcaf1supporting
confidence: 57%
See 1 more Smart Citation
“…This suggests the function of MUS81-EME1 down-regulation by Vpr is independent of its activity in G 2 arrest. An analysis of Vpr Q65R, another mutant defective in G 2 arrest (22,25,28,37), further supports this conclusion (Fig. 5, E and F).…”
Section: Vpr Down-regulates Mus81-eme1 By the Crl4-dcaf1supporting
confidence: 57%
“…In this case, down-regulation of the unknown factor(s) would activate ATR-mediated checkpoint signaling and induce G 2 arrest. In line with this hypothesis, mutagenesis studies have shown that a Vpr mutant with reduced DCAF1 binding, Q65R, lacks the ability to induce G 2 arrest (22,25,28,37). Furthermore, single mutation at Arg-80 (R80A) results in abrogation of Vpr-mediated G 2 cell cycle arrest without affecting DCAF1 interaction (10, 22, 25, 38 -40).…”
mentioning
confidence: 96%
“…A similar reversion has been observed in a laboratory worker accidentally contaminated with a vpr-deficient strain of HIV-1 (15,16). Several studies also reported mutations in the vpr gene in long-term nonprogressor (LTNP) patients (17)(18)(19)(20). Several lines of evidence indicate that Vpr interferes with DNA repair pathways (21).…”
supporting
confidence: 59%
“…A similar reversion was observed in a laboratory worker accidentally contaminated with a vpr-deficient strain of HIV-1 (36,37). Several researchers also reported mutations in the vpr gene in patients who were long-term nonprogressors (LTNP) (38)(39)(40)(41). Many activities have been described for Vpr.…”
supporting
confidence: 57%